Knowledge of Antimicrobial Stewardship Actions Among Out Patients at The Maitama District Hospital, Maitama, Abuja, Nigeria - Idoko, Lucy O.; Lolo, Nomsu S.; Okafor, Kingsley C. (British Journal of Healthcare and Medical Research, 2023)
Background: Antimicrobial stewardship programs primarily aim identify solutions to curb antimicrobial resistance (AMR). It helps to optimize antimicrobial use to improve patient outcomes, ensure cost-effective therapy, and reduce adverse sequel of antimicrobial use (including antimicrobial resistance) among residents, hospitalized patients, the public, and agricultural professionals. This study aims to assess the knowledge of antimicrobial stewardship actions among outpatients attending Maitama General Hospital, Abuja.Nigeria Methods: This was a descriptive cross-sectional study done between June and November, 2022 among 423 outpatients using Multistage sample technique. Data was collected using interviewer-administered structured questionnaire and analysed using the IBM SPSS 28 (Statistical Package for the Social Sciences). Ethical approval was granted by Bingham University Teaching Hospital, Ethics committee, Jos, Plateau State. Results: The level of knowledge about solutions to curb AMR (Antimicrobial stewardship) between male and female respondents showed 179 (44.75%) of female respondents had good knowledge, 28 (7.0%) had fair knowledge and 21 (5.25%) had poor knowledge. Of all the male respondents, 132 (33.0%) had good knowledge,12 ( 3.00)% had fair knowledge and 28 (7.00%) had poor knowledge. Summarily, 311 (77.75%) had good knowledge of antimicrobial stewardship, 40 (10.00%) had fair knowledge of antimicrobial stewardship and 49 (12.25%) had poor knowledge of antimicrobial stewardship. Conclusion: Majority of clients had good knowledge of antimicrobial stewardship actions, but this can be improved by planning and implementing more antimicrobial stewardship (AMS) sensitization activities in communities and among patients in the hospitals. Health care workers should have continuous professional development (CPD) training on AMS.